CHECKLIST OF THE ERIOPHYOID MITE FAUNA OF MONTENEGRO (ACARI: PROSTIGMATA: ERIOPHYOIDEA (Acta Entomologica Serbica, 2012)
Accounts are given of the eriophyoid fauna of Montenegro. Based on the literature records, a total of 156 mite species are listed from 130 host species of 42 plant families. The families Phytoptidae, Eriophidae and Diptilomiopidae are represented by 6, 138 and 12 species, respectively. Fifteen new species for science have been described from this area.